Aggregate Planning Implementation for Planning and Controlling The Materials in The Beverage Packaging Industry - Setiawan, Indra; Nurdiansyah, Nurdiansyah; Tosin, Muh.; Lusia, Vivi; Wahid, Muhammad (Spektrum Industri, 2022)
The Beverage Packaging Industry is a company that produce ready-to-drink drinks that produces Box Bottle Tea (BBT) 250 slim products. This product is sent to several customers and distributors throughout Indonesia. During 2020 the demand for this product has increased. In addition, the increasing demand also fluctuated significantly so the company was unable to predict production schedule. The continuity of the production process to meet consumer demand requires good production planning. The purpose of this research is to plan and control the production process of BBT 250 slim to obtain optimal raw material requirements. This study uses the method of Linear Regression and Aggregate Planning. Based on the analysis with Linear Regression, this study resulted in a model Y=319.575+3.723X, meaning that if demand decreases, the amount of production also decreases. This model is very useful for the Beverage Packaging Industry in planning and controlling raw materials for production. Calculation of raw material requirements for BBT 250 slim products results in an efficiency of raw materials than usual forecasting.